EFFECTIVENESS OF THE SINGING METHOD IN ARABIC VOCABULARY MEMORIZATION FOR FIRST GRADERS: FA‘ĀLIYYATU ṬARĪQATI AL-GHINĀ’ FĪ ḤIFẒ AL-MUFRADĀT AL-‘ARABIYYAH LADĀ TILMĪDHĪ AṢ-ṢAFF AL-AWWAL AL-IBTIDĀ’Ī - Satni; Siti Shalihah; Yuyun Rohmatul Uyuni (Muaddib: Journal of Arabic Language and Literature, 2025)
Songs can actually make the listener feel happy and calm when listening to it. Not only for refreshing, it turns out that singing can be used in learning Arabic so that students do not get bored quickly when learning. This research is a field research conducted at Madrasah Ibtidaiyah Ats-tsauroh Serang City. While the type of research is experimental research by dividing 2 class groups, namely the experimental class and the control class In its implementation, the experimental class and the control class are given a pre-test to find out the initial condition of whether there is a difference between the experimental class and the control class, then look for the effect of treatment through the post-test on both groups. This research uses a quantitative approach. Data obtained through tests, observations, and documentation. The results of this study indicate that there is a significant difference between the experimental class and the control class. This difference can be seen from the change in the average pre-test to post-test scores in each class (experimental class and control class). The average pre-test score was 45 and the post-test score was 85 in the experimental class, while in the control class the average pre-test score was 40 and the post-test score was 65. Thus it can be concluded that teaching Arabic vocabulary by using the singing method is proven effective to improve students' memorization of Arabic mufradat.